AGROWISATA KEBUN BUAH MANGUNAN DLINGO BANTUL - Sudiro, Syawal (Kepariwisataan: Jurnal Ilmiah, 2019)
The aims of this research is to know agrotourism sustainable development of Mangunan Garden. The reasons of developing agrotourism as such, it educates the purpose of keeping the relationship among local societies, interest sectors, and visitors. The Agrotourism of Mangunan Garden is inspired to improve the farmers earnings and the quality of rural society lives which then expletedly represent opportunity to educate th societies on agriculture an ecosystems. Agrotourism sustainable development of Mangunan Garden, embrases: geography, topography, elimate, type of vegetation (pine forest), in addition to destination which withdraw to visit, are Elephant Dlingo Cave, Pine Forest, Gardu Pandang, Cerme Cave, Makam Raja-Raja Panjimatan. Keywords : Agrotourism, Mangunan Garden, geography, topography, climate